Can We Quickly Retrieve Seismic Source Spectrum Characteristics After a Large Magnitude earthquake? Implementation of a Methodology Based on Coda Wave Analysis - Grendas, Ioannis; Theodoulidis, Nikos; Hollender, Fabrice; Hatzidimitriou, Panagiotis (Technical Annals, 2024)
After a large magnitude earthquake event, the direct estimation of its Seismic Source Spectrum (SSS) is important to estimate the energy content of the seismic source in broad-band frequency range. This direct knowledge of the SSS, except for the fact that can directly provide information about the Moment Magnitude of the earthquake, constitutes also, in frequency domain, that information, which is required to the Fourier Amplitude Spectra (FAS) simulation of the real-input seismic motion, in several target sites close to the source for which no earthquake recordings exist. In this study, the computation of the SSS of an earthquake is based on a single-station analysis algorithm by applying the spectral factorization method on the coda wave part of a seismic record. An application of this algorithm is implemented here for the Mw = 6.1 Cephalonia Island earthquake of 26/01/2014. The corresponding SSS, computed for several stations away from the source, are compared with the average SSS retrieved by standard applied method. The comparison results strongly encourage application and development of this SSS computation approach.